Beyond compliance: an onto-epistemic analysis of formative assessment practices in higher education - Suyo-Vega, Josefina Amanda; Meneses-La-Riva, Monica Elisa; Fernández-Bedoya, Víctor Hugo; Alvarado-Suyo, Sofía Almendra; Ocupa-Cabrera, Hitler Giovanni (Frontiers in Education, 2026)
Educational policies, aligned with the paradigm of change, position learning as the central axis of higher education, emphasizing assessment not only as a tool for measurement and monitoring but also as an object of pedagogical inquiry aimed at understanding students’ formative processes. This study sought to analyze the meaning of formative assessment in university settings from the perspective of research-oriented faculty, adopting an onto-epistemic approach. A qualitative methodology with a phenomenological design was employed, allowing for in-depth exploration consistent with the research objectives, data collection techniques, and instruments used. The theoretical framework drew on Guba and Lincoln to ground the constructivist paradigm, and on Vygotsky and Ausubel to examine teacher mediation and meaningful learning. The sample comprised ten professors with established research trajectories in education and university assessment. Data was collected through an interview guide, validated by experts, addressing conceptions, strategies, and instruments related to formative assessment. Findings revealed a lack of conceptual clarity regarding the meaning of formative assessment, even among experienced scholars, reflected in diverse and unarticulated practices. The study concludes that the gap between theoretical foundations and teaching practice sustains traditional schemes and restricts the development of essential competencies, underscoring the need to strengthen faculty epistemological and pedagogical training.